Fabrication of microfluidic devices for yeast culturing - Üçpınar, Sevda. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
Microfluidic technology has appreciated extensive success in recent years. Microfluidics is a well understood physic domain and can be used to develop tools for a wide range of platforms comprising engineering, biological applications and biotechnology. Some of the driving advantages for increased usage of microfluidics are small volumes of reagents and consumables, parallel processing, reduced processing time and high-throughput. Therefore, well-controlled microfluidic devices were designed for cell growth experiments. Saccharomyces cerevisiae has been an important model for studying cell biology in higher eukaryotic systems. Within the scope of this thesis, the fabrication of microfluidic devices for yeast culturing was achieved successfully. The microbioreactor was designed by L-Edit software to serve the purpose of cell trapping. Fabrication was done by hot embossing and thermo-compression bonding techniques. The microfluidic devices were fabricated from PMMA, COP and PEN polymers by optimizing the fabrication parameters for each of them separately. COMSOL Multiphysics3.5a program was used to simulate velocity, concentration and pressure distribution within the device. The main aim was to visualize the growth kinetics and expression of the GFP tagged Sld7p (YOR060C) of S.cerevisiae under environmental stress by changing nutrient media and the glucose concentration. The cell growth experiments were performed using either YNB (2% and 0.2% glucose contained) or YPD (2% glucose contained) media. During the experiments, brightfield and fluorescence microscope images were captured by Nikon Eclipse-T inverted microscope at regular time intervals and then processed via ImageJ-Fiji software. The results of cell count, area, perimeter and integrated density values were analyzed and used further to calculate the specific growth rates of yeast cells. The duration of budding and G1 phases in cell cycle were determined precisely. Using the in house fabricated Lab-on-a-Chip platform, cell culturing in the microbioreactor was achieved.
Keywords: Microfluidics.; Microfluidic devices.